Can Singapore's Development Model Be Successful in Rwanda? - Oğuzhan Bal (Uluslararası İlişkiler Çalışmaları Dergisi)
Singapore has become a country that attracts attention not only in its region but also around the world with its economic development success. The present study examines the reasons behind Singapore's success by focusing on Lee Kuan Yew's policies following his assumption of government in Singapore. It is evident that the implementation of a meritocracy approach by Yew resulted in the effective resolution of a significant national challenge, namely corruption. In addition, a comprehensive restructuring of the country's education and infrastructure was implemented with the objective of enhancing its global competitiveness. Moreover, he elevated the nation to a position of prominence in the global trade arena through the implementation of a free market economy and the strategic investment in ports. Similarly, the efforts of Paul Kagame following his rise to power in Rwanda in 2000 to prevent the country from reliving its past sufferings and to gain a respectable place in the international system are emphasized. Adopting the motto "Singapore of Africa", Kagame's approach centered on the development of technology and service sectors, with the objective of reducing the country's reliance on the agricultural economy. The two countries are evaluated and compared on the basis of similarities such as colonial past, geographical smallness and authoritarian leadership. The present study provides a comparative perspective to understand the intersection of local dynamics and global integration in the development strategies of disadvantaged Singapore and Rwanda. The study's central argument concerns the question of whether Rwanda, adopting Singapore as a paradigm of economic success, might also attain comparable levels of prosperity within the framework of authoritarian modernization theory.